(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
Following the bloody attacks on Washington and New York on September 11, 2001, the United States got involved in a Global War on Terror, GWOT, leading military forces to insist on dedicating most of their human resources and materials in the fight against Islamist fanaticism and extremism throughout the world, in particular in Afghanistan and Iraq. But the need to confront this specific type of adversary in these two scenarios, and within its particular context, led the armed forces to adopt a special form of military power, different from that which had traditionally been used to face a conventional adversary. Thus, the war on insurgency (COIN) in the last decade became the main focus for the American armed forces and for those from other western countries, with multiple implications in the organizational and doctrinal fields, and, above all, in the change of mindset of its participants, more prone to combat an adversary in symmetric terms, and with the application of maximum strength combat for a rapid and total destruction. In short, it meant a change in the paradigm of the preferred use of force in the military culture, and the way to wage war by the members of Western armies, particularly of the United States. Therefore, the adoption of what may be called the “COIN paradigm” has dominated the action of the American armed forces to fulfill their mission in Afghanistan and Iraq up to the strategic change imposed by the Obama administration in 2012, moment in which there was a redirection of priorities of the essential postulates of the security and defense policy of the United States toward the Asia-Pacific scenario. This has led one to question the current validity of the general principles identified in armed conflicts throughout history; in other words, the fundamentals of the theory on war that have controlled the organization, preparation, and equipment of armies in the past. This article intends to analyze the persistence of the nature of war in its traditional concept, within the context of the COIN paradigm, as the form of conflict that prevails presently. To do so, the theory of war of the famous Prussian philosopher Carl von Clausewitz, published in his major work On War, has been used as a basis for this study. Written during the first half of the 19th century, in light of his experiences and reflections about the Napoleonic campaigns, it is still a required reference for all studies regarding the nature of war. This theory is analyzed in view of the basic principles of today’s predominant adversary: insurgency, with COIN as the strategy to combat it. The hypothesis for the development of this analysis is that war, in the sense of the struggle between the will of two adversaries to prevail, through the use of force, has intrinsic principles and a logic that are identifiable and can also be extended to the dynamics which are characteristic of a COIN struggle. The analysis undertaken will lead to the development of conclusions regarding the degree of applicability of the premises characteristic of a theory of war, such as the one of the famous Clausewitz in the struggle against insurgency and, with it, if the theory of the brilliant Prussian is still valid in a COIN context. In short, whether the death certificate of the famous Prussian should be issued, or he is still alive and in good health.